Twits - Dahl, Roald; Blake, Quentin (Penguin Books Ltd, 2016)
The Twits by Roald Dahl is a humorous children's book that follows the misadventures of a nasty, mean-spirited couple, Mr. and Mrs. Twit. They delight in playing cruel pranks on each other and mistreating the animals they keep, particularly a family of monkeys, the Muggle-Wumps, whom they force to live upside down. Eventually, the clever monkeys, with the help of some birds, devise a plan to turn the tables on the Twits. In the end, the Twits' cruelty backfires, leading to their downfall in a comically satisfying way. The book highlights themes of kindness, cleverness, and justice.